K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 6 2016

x(x+1)(x+6)-x^3=5x

(x^2+x)(x+6)-x^3=5x

x^3+6x^2+x^2+6x-x^3-5x=0

7x^2+x=0

x(7x+1)=0

x=0 hoặc 7x+1=0<=> x=-1/7

17 tháng 5 2016

e)(3x-1)(2x+7)-(x+1)(6x-5)=16

=>\(6x^2-2x+21x-7-6x^2-6x+5x+5\)=16

=>18x-2=16

=> 18x=18

=> x=1

17 tháng 5 2016

b)\(x\left(x+1\right)\left(x+6\right)-x^3=5x\)

=>\(x\left(x+1\right)\left(x+6\right)-x^3-5x=0\)

=> \(x\left(x^2+x+6x+6\right)-x\left(x^2-5\right)=0\)

=>\(x\left[\left(x^2+7x+6\right)-\left(x^2-5\right)\right]=0\)

=> __x=1

     |__7x+1=0=> 7x=-1=> x=-1/7

26 tháng 3 2018

\(x^2+5x+6=0< =>x^2+2x+3x+6=0< =>x\left(x+2\right)+3\left(x+2\right)=0< =>\left(x+3\right)\left(x+2\right)=0< =>\left[{}\begin{matrix}x+2=0\\x+3=0\end{matrix}\right.< =>\left[{}\begin{matrix}x=-2\\x=-3\end{matrix}\right.\)

26 tháng 3 2018

cố quên một người: chưa hiểu chỗ nào vậy